Model Loyalitas Nasabah: Pengaruh Pengalaman Pelanggan dan Kualitas Pelayanan Melalui Citra Merek - Fajar Maulana; Pamuji Gesang Raharjo; Meylani Tuti (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the influence of customer experience and service quality on customer loyalty with brand image as an intervening variable at PT Jaminan Pembiayaan Askrindo Syariah. The research is motivated by the importance of building customer loyalty in the sharia financing industry through improving customer experience, service quality, and strengthening brand image as strategic factors that can create long-term relationships with customers. The study uses a quantitative approach with a survey method. Primary data was obtained by distributing questionnaires to 200 customers of PT Jaminan Pembiayaan Askrindo Syariah selected using a purposive sampling technique. Data analysis was carried out using Partial Least Squares–Structural Equation Modeling (PLS-SEM) assisted by SmartPLS software version 3. Testing includes evaluation of the outer model (validity and reliability), the inner model, and hypothesis testing through bootstrapping techniques. The results show that customer experience has a positive and significant effect on brand image with a t-value of 8.213 >1.96 and customer loyalty with a t-value of 8.783 >1.96. Service quality also has a positive and significant effect on brand image with a t-value of 11.451 > 1.96 and customer loyalty with a t-value of 6.595 > 1.96). Furthermore, brand image is proven to have a positive and significant effect on customer loyalty with a t-value of 13.422 > 1.96. The results of the mediation test indicate that brand image is able to mediate the influence of customer experience on customer loyalty (with a t-value of 6.015 > 1.96) and mediate the influence of service quality on customer loyalty with a t-value of 7.675 > 1.96. The contribution of this study lies in strengthening empirical evidence regarding the strategic role of brand image as a mediating mechanism in the relationship between customer experience, service quality, and customer loyalty in the Islamic financing industry. The research findings are expected to provide input for the management of PT Jaminan Pembiayaan Askrindo Syariah in formulating strategies to improve service quality, manage customer experience, and strengthen brand image to create sustainable customer loyalty.